Intergenerational Value Shift from Traditional to Secular-Rational Values in Lithuania - Žiliukaitė, Rūta (Sociologija. Mintis ir veiksmas, 2007)
The analysis of value changes in contemporary Lithuanian society, presented in this article, is based on insights of Ronald Ingelhart, that transition from a traditional, agrarian society to industrial society is accompanied by the changes in worldviews, reflected in value shift from traditional values, emphasizing traditional authority, importance of religion, family and community, to secular-rational values, emphasizing independence and autonomy of individual. Using data of European Value Surveys and World Values Surveys conducted in Lithuania from 1990 to 2005, the author of the article seeks to reveal intergenerational value differences between generations that grew up before Second World War and generations, that reached adulthood during years of Soviet regime, between generations that grew up in still agrarian Lithuania and generations that grew up in more industrialized and urbanized Lithuania. Data analysis, presented in the article, show that intergenerational differences in value orientations form one dimension of value change, related to 20th century modernization processes in Lithuania.